Evaluation of the antigenicity of universal epitopes from PvDBPII in individuals exposed to Plasmodium vivax malaria (2010)
The Duffy-binding protein (PvDBP) mediates invasion of reticulocytes by the malaria parasite Plasmodium vivax. PvDBP has been recognized as a good vaccine candidate due to its ability to induce antibody responses capable of inhibiting target cell invasion after natural infections. For the development of subunit-based vaccines, it is important to identify universal epitopes that could be presented by different HLA-DR alleles to induce effective cellular and humoral immune responses. In this study, the antigenicity of universal epitopes from PvDBPII was evaluated by stimulating peripheral blood mononuclear cells (PBMCs) isolated from individuals with different degrees of P. vivax malaria exposure and distinct HLA-DR alleles. Peptides 1635 and 1638 induced lymphoproliferation and stimulated the production of IL-6 and IFN-?. The results suggest that conserved peptides binding with high activity to red blood cells and with known affinity to HLA-DR proteins could be good components for a P. vivax vaccine. © 2010 Institut Pasteur.